Characteristics of Atrial Fibrillation Based On Age, Sex, and Etiology - Barizatul Husniyah; Bambang Herwanto; Noor Idha Handajani (JUXTA: Jurnal Ilmiah Mahasiswa Kedokteran Universitas Airlangga, 2020)
Introduction: Atrial fibrillation (AF) is one type of arrhythmia that occurs frequently to patients in the last decade. AF patients have five times higher risk to stroke and death, and they also have two times higher risk compared to others. A correct selection of governance in AF could result in better prognosis of the patients. The aim of this study was to explain AF of the outpatients in Department of Cardiology of Dr. Soetomo General Hospital Surabaya in February 2018, so that it can detect early AF and prevent further advanced complications. Methods: This research was descriptive method design. The population and sample of this study included all of the patients who had AF and came to out-patient care in Department of Cardiology of Dr. Soetomo General Hospital Surabaya in February 2018. This research was real-time total sampling and was analyzed descriptively.Results: In this study, 60 samples which were suitable to the criteria were gained with the numbers of 25 males (41.7%) and 35 females (58.3%). AF attacked more patients in age 51-60 years old (31.7%). The most common etiology of AF is rheumatic heart disease (60%).Conclusion: Most of AF patients in this study were 51-60 years old, female, and were caused by rheumatic heart disease. With the lack information, it still needed further studies with more complete data for better accuracy.